Ultimate design of unbound granular base courses for flexible pavements - Jitsangiam, Peerapong; Nikraz, Hamid; Siripun, Komsun (American Society of Civil Engineers (ASCE), 2011)
This study aims to introduce alternative design procedures for a flexible pavement base course by utilizing ultimate strength criteria with the sophisticated laboratory results of base course materials. Based on the design protocol, only the design criteria of the horizontal tension and the vertical compression occur at the bottom of the asphalt layer and at the top of the subgrade, respectively are employed. The real behavior of a base course under traffic loads has been rarely accounted into the pavement design protocol. Nowadays, traffic is growing in terms of magnitude and frequency far beyond the past causing premature deterioration in base course layers leading to major damage in pavements. The study presents theoretically a more suitable approach of stress and strain distributions in a flexible pavement using the finite element method. The effects of uniform design pressure and material attributes generated when a vehicle travels, namely the stress and strain contributions between tires and pavement layers, were investigated. Moreover, new design criteria for an unbound granular layer were defined as the ultimate strength design and the bearing capacity factor resulting from the application of the shallow foundation bearing capacity concept within the California Bearing Ratio (CBR) results.